Sol-Gel Processing for Conventional and Alternative Energy - Aparicio, Mario; Jitianu, Andrei; Klein, Lisa C. (Advances in Sol-Gel Derived Materials and Technologies,, 2012)
Sol-Gel Processing for Conventional and Alternative Energy is a comprehensive source of information on the use of sol-gel processing in materials in energy systems, conversion, storage, and generation. The volume editors include numerous applications, primarily in nuclear fuel processing, electrolytes for fuel cells, and dye-sensitized solar cells (DSSC). In addition to examining contemporary processing, properties, and industrial applications, Sol-Gel Processing for Conventional and Alternative Energy identifies materials challenges presented by conventional and alternative energy generation that require new materials and innovative processing. Each chapter is written by an internationally respected researcher. The book provides a state-of-the-art treatment of different aspects of materials for energy production, with a focus on processing, and covers related topics such as carbon sequestration, clean energy, and biofuels. This book also: Organizes the information about sol-gel processing in energy systems into one volume Addresses energy applications of materials both in terms of energy conversion and in terms of energy storage Discusses the role of sol-gel processing in meeting the challenge of making solar energy affordable Address other ways to make conventional energy and alternative energy affordable and clean Sol-Gel Processing for Conventional and Alternative Energy is ideal for researchers working in industry, academia, and national laboratories with interest and professional competence in materials for energy storage and energy conversion. This book will also be useful to senior year and graduate students pursuing a degree in chemistry, electrochemistry, solid state physics,chemical engineering, materials science and engineering, and mechanical engineering.